Benign Enhancing Foramen Magnum Lesions: Clinical Report of a Newly Recognized Entity - McGuinness, B.J. (AJNR Am J Neuroradiol, 2017)
Intradural extramedullary foramen magnum enhancing lesions may be due to meningioma, nerve sheath tumor, aneurysm, or meningeal disease. In this clinical report of 14 patients, we describe a novel imaging finding within the foramen magnum that simulates disease. The lesion is hyperintense on 3D-FLAIR and enhances on 3D gradient-echo sequences but is not seen on 2D-TSE T2WI. It occurs at a characteristic location related to the posterior aspect of the intradural vertebral artery just distal to the dural penetration. Stability of this lesion was demonstrated in those patients who underwent follow-up imaging. Recognition of this apparently benign lesion may prevent unnecessary patient anxiety and repeat imaging.